Roman Female Writers for Literary Education in Latin II - San Juan Manso, Enara (Didáctica. Lengua y Literatura, 2022)
Although literature was in Rome almost exclusively an activity of men, also some Roman women came to express themselves through written word. We only keep isolated texts or fragments of these female writers, which do not usually receive the attention of anthologies and Latin literature handbooks. In this work, we analyze how the study of literature is oriented in the curriculum of Latin II of 2nd Baccalaureate and we make a proposal to contribute to literary education through the inclusion of texts by these women in the subject.
Keywords: Roman Female Writers; Latin Literature; Women’s Inclusion; Literary Education; Baccalaureate